Mecanismos, processos e democracias : a sociologia histórica de Charles Tilly e a história breve mas turbulente de um lago - Rosas, António (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
Compared to its alternatives, the claims that democracies result from the material-economical modernisation, the incarnation of a certain type of political culture or the institutional objectivation seem to be less and less reasonable. The aim of this article is not only to familiarise the reader with one of the most promising theoretical perspectives of contemporary comparative historical sociology – that of Charles Tilly – but also to demonstrate how a processual analysis of political regimes is the more suitable to understand and improve today’s real democracies.